Computational finite element methods in nanotechnology - Musa, Sarhan M. (Boca Raton, Fla. : CRC Press, 2013)
'This book provides an introduction to the key concepts of computational finite element methods (FEMs) used in nanotechnology in a manner that is easily digestible to a new beginner in the field. It provides future applications of nanotechnology in technical industry. Also, it presents new developments and interdisciplinary research in engineering, science, and medicine. The book can be used as an overview of the key computational nanotechnologies using FEMs and describes the technologies with an emphasis on how they work and their key benefits, for novices and veterans in the area'--
1. Overview of computational methods in nanotechnology / Orion Ciftja and Sarhan M. Musa -- 2. Finite element method for nanotechnology applications in nano-/microelectronics / Jing Zhang -- 3. Modeling, design, and simulation of N/MEMS by integrating finite element, lumped element, and system level analyses / Jason Vaughn Clark, Prabhakar Marepalli, and Richa Bansal -- 4. Nanorobotic applications of the finite element method / S. Sadeghzadeh ... [et al.] -- 5. Simulations of dislocations and coherent nanostructures / Anandh Subramaniam and Arun Kumar -- 6. Continuum and atomic-scale finite element modeling of multilayer self-positioning nanostructures / Y. Nishidate and G.P. Nikishkov -- 7. Application of finite element method for the design of nanocomposites / Ufana Riaz and S.M. Ashraf -- 8. Finite element modeling of carbon nanotubes and their composit / Mahmoud Nadim Nahas -- 9. Finite element-aided electric field analysis of needleless electrospinning / Haitao Niu, Xungai Wang, and Tong Lin -- 10. Molecular dynamic finite element method (MDFEM) / Lutz Nasdala, Andreas Kempe, and Raimund Rolfes -- 11. Application of biomaterials and finite element analysis (FEA) in nanomedicine and nanodentistry / Andy H. Choi ... [et al.] -- 12. Application of finite element analysis for nanobiomedical study / Viroj Wiwanitkit -- 13. Finite element method for micro- and nano-systems for biotechnology / Jean Berthier -- 14. Design of the nanoinjection detectors using finite element modeling / Omer G. Memis and Hooman Mohseni -- 15. Finite element method (FEM) for nanotechnology application in engineering : integrated use of macro-, micro-, and nano-systems / Radostina Petrova, P. Genova, and M. Tzoneva -- 16. Modeling at the nano level : application to physical processes / Serge Lefeuvre and Olga Gomonova.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Nanotechnology -- Mathematics; Finite element method